Effects of Oxidized Soybean Meal and Oxidized Soybean Oil on the Muscle Oxidative Stability, Flesh Quality, Amino Acid Profile, and Fatty Acid Profile of Megalobrama amblycephala - Yangyang Huang; Xiufei Cao; Wenbin Liu; Guangzhen Jiang; Aimin Wang (MDPI AG, 2024)
This study aimed to investigate the effects of oxidized soybean meal and oxidized soybean oil on the muscle oxidative stability, flesh quality, amino acid profile, and fatty acid profile of blunt snout bream Megalobrama amblycephala. Oxidized soybean meal and oxidized soybean oil were obtained from fresh soybean meal (FSM) and fresh soybean oil (FSO) by heating. In the experimental diet, the proportions of oxidized soybean meal (OSM) and oxidized soybean oil (OSO) were 30% and 4.19%, respectively. The feeding trial was conducted for 8 weeks. The findings revealed that both OSM and OSO reduced glutathione peroxidase (GSH-Px), superoxide dismutase (SOD), catalase (CAT), hardness, chewiness, and oxymyoglobin (OxyMb) and elevated the content of malondialdehyde (MDA), protein carbonyl (PC), and metmyoglobin (MetMb) in the muscle. OSM notably decreased the content of muscle essential amino acids (EAAs), nonessential amino acids (NEAAs), delicious amino acids (DAAs), and total amino acids (TAAs) compared with CON and OSO. Compared with CON and OSM, OSO significantly reduced the content of elaidic acid (C18:1n9t), linoelaidic acid (C18:2n6c), polyunsaturated fatty acids (PUFAs), ω-6 PUFAs, and the ratio of ω-6/ω-3, while stearic acid (C18:0), γ-linolenic acid (C18:3n6) and saturated fatty acids (SFAs) were significantly elevated. In conclusion, this study demonstrated that both OSM and OSO negatively impacted muscle antioxidant capacity and flesh quality. Moreover, OSM adversely affected the amino acid profile of the muscle, while OSO impaired the fatty acid profile.